RFID in the Retail sector: A Bibliographic review of the literature - Bruno Valdivia, Giordano Sebastian (2022)
All of the companies in the Retail sector, regardless of their size and age, have suffered from different problems related to their stock, some of those problems could be explained by the bullwhip effect or problems in the replenishment policies, such problems are also known as Inventory Record Inaccuracy (IRI), which complicates supply chain management and intensifies inventory losses both materially and financially. To mitigate the damage, radio frequency identification (RFID) can be used, but at a certain degree and not in most companies. The results show the countries with the highest literary production which is related to how deep the RFID technology is as well as the authors, the most used keywords and the magazines where they are published.